Performance of Legumes on Weed Suppression with Hybrid Maize Intercropping - Naher, Q; Karim, SMR; Begum, M (Bangladesh Agronomy Journal, 2019)
Field experiment was carried out at the Bangladesh Agricultural Research institute, Joydebpur, Gazipur during 2010 to 2011 to identify suitable legume crops with maize in maize + legume intercropping systems for better weed suppression, productivity and economic benefits in Rabi season. There were 17 treatments of which two sole crop of hybrid maize (Zea mays BARI Hybrid bhutta -9) (weed free and no weeding), three weed free sole crops of pea (SN), bushbean (SN) and cowpea (SN) in Rabi season, and their intercropping. Twelve intercropping with different weeding regimes (no weeding, one hand weeding at 20 days after emergence (DAE), one hand weeding at 40 DAE, and two hand weeding at 20 and 40 DAE of maize-legume intercropping under normal row (75 cm Î 25 cm), and two rows of legumes in between two rows of maize were used . Among all intercropping, maize-pea with two hand weeding at 20 and 40 DAE gave the lowest (6.57 g m-2 at harvest) weed dry weight and the highest weed control efficiency (86% at harvest). Maize-pea with two hand weeding at 20 and 40 DAE gave the highest yield (maize: 7.58 t ha-1; 6.27 t ha-1 pea), resource complementarily and profitability (LER = 1.89, BCR = 4.19). Intercropping of two rows of pea in between two rows of maize with two hand weeding at 20 and 40 DAE to be a promising practice for weed suppression and profitable maize + legume intercropping in Rabi season. Bangladesh Agron. J. 2018, 21(2): 33-44